2023
DOI: 10.1590/1678-4499.20220218
|View full text |Cite
|
Sign up to set email alerts
|

Corn straw return effectively improves the stability and increases the carbon and nitrogen contents of waterstable aggregates in northeastern China black soil

Abstract: In view of the current situation of black soil degradation, straw return as an important conservation tillage measure has been extensively promoted. Based on 15 N tracing technology, this paper carried out experiments of different straw returning modes, including CK (conventional fertilizing tillage with straw-free returning), straw mulching (i.e., M), straw mixed with topsoil (i.e., T), and straw deep incorporation (i.e., D), to explore the influence of straw returning on the distribution and stability, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Our findings revealed that macro-aggregates (> 2 mm) were dominant in all soil layers. In accordance, a significant increase of approximately ∼11 % appeared in the contents of soil macro-aggregates via straw returning coupled with the conventional (SF) and or 80 % conventional fertilization (SDF) compared with the F treatment [ 29 ]. This is consistent with the results of Zhao et al [ 21 ], suggesting a higher structural/aggregate stability in the study straw amended soils [ 13 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our findings revealed that macro-aggregates (> 2 mm) were dominant in all soil layers. In accordance, a significant increase of approximately ∼11 % appeared in the contents of soil macro-aggregates via straw returning coupled with the conventional (SF) and or 80 % conventional fertilization (SDF) compared with the F treatment [ 29 ]. This is consistent with the results of Zhao et al [ 21 ], suggesting a higher structural/aggregate stability in the study straw amended soils [ 13 ].…”
Section: Discussionmentioning
confidence: 95%
“…It is also worth noting that in situ straw returning provides fresh organic substrate for soil microorganisms [ 34 ]. This can improve the microbial decomposition of soil organic matter, that in turn accompanies by large productions of polysaccharide metabolites and humic substances [ 14 , 29 ]. The latter contribute to the formation of larger and more stable aggregates [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation